Teachers’ preparedness for implementing the Educational Coding and Robotics curriculum in South Africa - Zivanayi, William; Malinga, Serah Ntombikayise (African Journal of Teacher Education, 2025)
It is a significant step that the Department of Basic Education has taken to integrate educational coding and robotics into the mainstream school curricula in a world where technology is a normal element of everyday life. A deeper examination of the schools' and teachers' readiness to adopt this new curriculum is significant to improve learning and boost active teaching techniques. The article aimed to examine the teachers’ preparedness, interests, knowledge, and self-confidence in implementing the newly introduced learning area – Educational coding and robotics in the mainstream school curriculum. This study was framed in the Unified Theory of Acceptance and Use of Technology. Using a systematic review approach,  articles obtained from PubMed, Embase, Google Scholar, Scielo, Scopus, and ERIC were critically analyzed to identify descriptive themes and analytical themes. The review showed that the attitudes of South African teachers on ECR hinge on the availability of resources, pedagogical computer skills, teachers’ technological beliefs, and the management team's influences on technology. DBE needs to work closely with the teachers’ training institutions and pedagogical experts to meet the needs of teachers and learners regarding educational coding and robotics curriculum. Engagement with teachers may increase their knowledge, skills, attitudes, and values for them to have a meaningful contribution to the educational coding and robotics curriculum.